(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Due to its prolonged detection window, hair has become an important material for drug analysis. It is suitable for the detection of frequent drug abuse (DOA) dependence and other toxicological considerations. The advancement in chromatographic techniques especially liquid chromatography-tandem mass spectrometry (LC/MS-MS) makes detecting even traces of a drug in hair possible. Therefore, LC/MS-MS is progressively replacing gas chromatographic techniques as a tool for screening and confirmation making it the method of choice for hair analysis. In the present study, a method to determine common drugs of abuse in hair samples is described. Human hair was tested for a range of different classes of drugs of a forensic and toxicological nature including selected amphetamines, cannabinoids, and benzodiazepines. For extraction purposes, the hair samples were decontaminated using dichloromethane, grounded, and treated with 1 M sodium hydroxide, followed by n-hexane/ethyl acetate extraction using liquid-liquid extraction (LLE). Following extraction from hair samples, drug screening employed liquid chromatography coupled with tandem mass spectrometric (LC/MS-MS). The screening method (for >20 drugs) was calibrated with a tailored drug mixture and was validated for 11 selected drugs for this study. A shim-pack FC-ODS (2.0 mm I.D. x 150 mm L, 3 µm) column was used for analysis. The total instrument run time was 30 minutes with no noted matrix interferences. Hair samples were screened using this new method and samples were confirmed positive for several drugs, mainly drugs of abuse. The LC/MS-MS method described in the present study has proved to be simple and robust for the determination of drugs in hair. It is currently used for real samples in the Forensic Laboratory of Jordan.